A Call to Address RN, Social Work, and Advanced Practice Registered Nurses in Nursing Homes: Solutions From the Missouri Quality Initiative. Issue 1 (January 2022) - Popejoy, Lori L.; Vogelsmeier, Amy A.; Canada, Kelli E.; Kist, Shari; Miller, Steven J.; Galambos, Colleen; Alexander, Gregory L.; Crecelius, Charles; Rantz, Marilyn
Abstract : Background: US nursing homes (NHs) have struggled to overcome a historic pandemic that laid bare limitations in the number and clinical expertise of NH staff. Problem: For nurse staffing, current regulations require only one registered nurse (RN) on duty 8 consecutive hours per day, 7 days per week, and one RN on call when a licensed practical/vocational nurse is on duty. There is no requirement for a degreed or licensed social worker, and advanced practice registered nurses (APRNs) in NHs cannot bill for services. Approach: It is time to establish regulation that mandates a 24-hour, 7-day-a-week, on-site RN presence at a minimum requirement of 1 hour per resident-day that is adjusted upward for greater resident acuity and complexity. Skilled social workers are needed to improve the quality of care, and barriers for APRN billing for services in NHs need to be removed. Conclusions: Coupling enhanced RN and social work requirements with access to APRNs can support staff and residents in NHs.